Assessing the Effect of Underground Void on Strip Footing Sitting on a Reinforced Sand Slope with Numerical Modeling - Mazouz, B.; Mansouri, T.; Baazouzi, M.; Abbeche, K. (Engineering, Technology & Applied Science Research, 2022)
This paper presents the results of the numerical analysis undertaken to investigate the effect of the underground void on the load-bearing capacity of a strip footing placed on an unreinforced and geogrid-reinforced sand slope with a void inside. The failure mechanism of the soil was also investigated. The numerical model was obtained using 2D plane-strain FEM analysis (in Plaxis software), in which the nonlinear Mohr-Coulomb model was utilized. The effects of various parameters such as the number of geogrid layers (N), the vertical distance ratio between the top of the cavity from the base of footing (H/B), the horizontal distance of void centerline to the footing center (X/B), on the behavior of footing are studied in this research. The results indicate that there is a critical zone under the footing in which the existence of void has no influence on the bearing capacity and stability of the footing. In addition, the use of geogrid reinforcement reduces the settlement and enhances bearing capacity. Finally, the bearing capacity factor and failure mechanism increase with increasing horizontal and vertical void distances ratios (X/B and H/B) and reinforcement layers.